Μ‐NMR at the point of care testing. Issue 5 (15th January 2020) - Guo, Jiuchuan; Jiang, Di; Feng, Shilun; Ren, Chunhui; Guo, Jinhong
Abstract: NMR shows strong analytical capability for obtaining molecular information on materials and is used in a variety of fields. Micro‐NMR (µNMR) is mainly based on low‐field NMR (LF‐NMR), which makes NMR detection portable and inexpensive. Point‐of‐care testing (POCT) has gradually become an area of major concern, and scientists have made much progress in applying µNMR systems for POCT. To the best of our knowledge, this is the first review of the latest development in miniaturization of µNMR systems. Then, we discuss cutting‐edge µNMR‐based applications in POCT and the outlook for future developments.